Assortative Mating and Household Inequality - Vo, Quoc Thai; Lichard, Tomáš; Mazouch, Petr, 1981-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
This thesis investigates the role of educational assortative mating in shaping household income inequality in the Czech Republic, with comparative insights from Spain and Sweden. Using harmonized EU-SILC microdata for the years 2005–2023, the analysis identifies real heterosexual couples, classifies them by educational match type, and evaluates income disparities through descriptive statistics, inequality measures (Gini, S80/S20), counterfactual simulations, and regression-based decomposition. The results show that educational homogamy is both prevalent and economically advantageous in Czechia, with homogamous couples earning significantly more than hypergamous or hypogamous unions. Counterfactual simulations confirm that assortative mating contributes to higher income inequality than would occur under random matching. While this inequality effect has declined over time, it remains substantial. Compared to Spain and Sweden, the Czech Republic exhibits moderate but persistent inequality patterns driven by educational sorting. These findings underscore the importance of partner selection in household income formation and highlight its implications for social stratification and policy in societies.
Vedoucí práce: Tomáš Lichard
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: data analysis and modeling [obor dipl. práce]; diplomové práce; master's theses